Pedagogical Leadership and the Implementation of Project-Based Curriculum: Impact on Students' Problem-Solving Abilities in Australia - Maria Santos; Rajesh Gupta; Sofia Petrova (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2025)
This study explores the impact of pedagogical leadership and the implementation of project-based learning (PBL) on students' problem-solving abilities in Australia. In the context of modern education marked by the challenges of globalization and technological advancement, the PBL approach has proven to enhance student engagement in the learning process through real-world projects that promote critical thinking and problem-solving skills. Pedagogical leadership, which includes support from school management and a culture of collaboration, plays a crucial role in fostering innovation in the implementation of PBL. This study employs qualitative methods, including in-depth interviews, observations, and document analysis, to gain a comprehensive understanding of how PBL is applied and its effects on students' problem-solving abilities. The research findings indicate that supportive pedagogical leadership, which encourages innovation and collaboration among teachers as well as parental involvement, can enhance student motivation and create a conducive learning environment. However, challenges such as limited teacher training and difficulties in integrating projects with national curriculum standards pose obstacles to the effective implementation of PBL. The study concludes that successful PBL implementation requires support from strong school leadership, provision of resources, and training for teachers. These findings have significant implications for education policy in Australia, particularly in designing a more relevant curriculum that prepares students to face real-world challenges.